Eurasian Financial Markets, Macrofoundations Underneath Development Outlook : How Has the Global Financial Crisis Altered Perspectives of Kazakhstan Stock Exchange? - Nowak, Dominik (Makrofundamenty rozwoju rynków finansowych Eurazji : w jaki sposób kryzys finansowy wpłynął na perspektywy rozwoju giełdy papierów wartościowych w Kazachstanie?, 2010)
The Kazakh Stock Exchange aims to be the leading stock market in Eurasia. In fact, the enormous exertion was taken to transform this former Soviet Republic into a place where influence and interests of many different parties, transactions involving not only commodities or raw materials but human capital or sophisticated financial instruments would meet. Due to after-effects of the recent global financial crisis Kazakh stock market suffered heavy losses and proven to be illiquid and very unstable. It struggled not only to attract foreign investors, but even own domestic companies, preferring to seek for financing on UK and US stock markets, listing GDR's rather than equity stocks on KASE. The purpose of this paper is to bring to the light advantages and drawbacks, strengths and weaknesses of this unique market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 116-126
Keywords: Kazakhstan Stock Market; Eurasian Financial Sector; Macrofoundations; KASE